دور الشيطان في مسار الإنسان من خلال آيات قصّة آدم = The role of satan in the pathway of human in the shade of the story of Adam - Makhlouf, Hussam Eddine; Elatrash, Radwan Jamal Yousef (Department of Quran and Sunnah Studies, Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University, Malaysia, 2018)
This research deals with and analyses the role of Satan in the pathway of man in the shade of the story of Adam. The significance of this theme lies in its attempt to display the main implications underlying the rationale behind the creation of man and alerting him against the stages of temptations by Satan. It also attempts to guide man and entrust him with the maintenance and governance of the earth. The study uses inductive method in selecting the Qur´Énic verses and exegeses (interpretations) pertaining to the temptations of Satan and the recurrent repentance of man and his offspring. It uses analytical method to extrapolate the most important implications about the temptations of man by Satan, and how to avoid them. The researcher has concluded several results, the most important of which are: that the story of Adam has designed a life path for man and made apparent the role of Satan in hindering his way in life, that the results contain key guidelines that can serve as a guide and pathway for man in his journey to God.